1997
DOI: 10.1017/s0033291796004643
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of psychotic disorders in migrants from the Caribbean to the United Kingdom

Abstract: The size of the increase and the methodological safeguards employed support the validity of this now highly replicated finding. A personal or family history of migration from the Caribbean is a major risk factor for psychosis; the consistency of this finding justifies a systematic evaluation of potential aetiological factors. Any hypothesis derived from the evidence so far must explain: increased incidence in first and second generation migrants; increased risk for all psychoses (including affective psychoses)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
120
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(129 citation statements)
references
References 13 publications
7
120
2
Order By: Relevance
“…In both regards, these findings are consistent with the acculturative stress hypothesis, the suggestion that stressors associated with being an immigrant increase risk for psychopathology (Rogler et al, 1991;Vega et al, 1998;Escobar and Vega, 2000;Grant et al, 2004). These findings are also consistent with studies in the US (Odegaard, 1932;Malzberg and Lee, 1956), Europe (Harrison et al, 1997;Selten et al, 1997;Selten et al, 2001;Zolkowska et al, 2001;Cantor-Graae and Selten, 2005), and Australia (Krupinski and Stoller, 1965) that have found increased risk for psychotic disorders among immigrants.…”
Section: Discussionsupporting
confidence: 86%
“…In both regards, these findings are consistent with the acculturative stress hypothesis, the suggestion that stressors associated with being an immigrant increase risk for psychopathology (Rogler et al, 1991;Vega et al, 1998;Escobar and Vega, 2000;Grant et al, 2004). These findings are also consistent with studies in the US (Odegaard, 1932;Malzberg and Lee, 1956), Europe (Harrison et al, 1997;Selten et al, 1997;Selten et al, 2001;Zolkowska et al, 2001;Cantor-Graae and Selten, 2005), and Australia (Krupinski and Stoller, 1965) that have found increased risk for psychotic disorders among immigrants.…”
Section: Discussionsupporting
confidence: 86%
“…It remained uncertain whether these increased rates extended to all psychotic disorders and to all ethnic minority groups in the UK. Some studies have suggested increased rates of schizophrenia in Africans (van Os et al 1996), but findings for Asians have been contradictory (King et al 1994 ;van Os et al 1996;Bhugra et al 1997 ;Harrison et al 1997). The EMPIRIC study (King et al 2005), a community-based prevalence study, found a more modest association between ethnicity and the likelihood of reporting psychotic symptoms.…”
Section: Previous Studiesmentioning
confidence: 99%
“…stress symptoms among voluntary migrants (Harrison et al, 1997;Noh & Avison, 1996) and refugees (Beiser, 1999;Eaton & Garrison, 1992;Porter & Haslam, 2001Rumbaut, 1991), its applicability to project-induced migrants, a different type of involuntary migrants, has seldom been demonstrated. This study tests the hypotheses that anticipation of project-induced migration is a stressor which would negatively affect the mental well-being of migrants and that migrants with more protective resources should be less adversely affected.…”
mentioning
confidence: 99%